From Biology to Drug Development: New Approaches to Combat the Threat of Fungal Biofilms - Pierce, Christopher G. (Microbiol Spectr, 2015)
Fungal infections constitute a major threat to an escalating number of critically ill patients. Fungi are eukaryotic organisms and, as such, there is a limited armamentarium of antifungal drugs, leading to high mortality rates. Moreover, fungal infections are often associated with the formation of biofilms, which contribute to virulence and further complicate treatment due to the high level of antifungal drug resistance displayed by sessile cells within these microbial communities. Thus, the treatment of fungal infections associated with a biofilm aetiology represents a formidable and unmet clinical challenge. The increasing importance and awareness of fungal biofilms is reflected by the fact that this is now an area of very active research. Studies in the last decade have provided important insights into fungal biofilm biology, physiology and pathology, as well as into the molecular basis of biofilm resistance. Here we discuss how this accumulated knowledge may inform the development of new anti-biofilm strategies and therapeutics that are urgently needed.